2016
DOI: 10.1038/srep22908
|View full text |Cite
|
Sign up to set email alerts
|

In silico assessment of primers for eDNA studies using PrimerTree and application to characterize the biodiversity surrounding the Cuyahoga River

Abstract: Analysis of environmental DNA (eDNA) enables the detection of species of interest from water and soil samples, typically using species-specific PCR. Here, we describe a method to characterize the biodiversity of a given environment by amplifying eDNA using primer pairs targeting a wide range of taxa and high-throughput sequencing for species identification. We tested this approach on 91 water samples of 40 mL collected along the Cuyahoga River (Ohio, USA). We amplified eDNA using 12 primer pairs targeting mamm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 48 publications
2
79
0
Order By: Relevance
“…In addition, inter-specific differences in the edit distance were calculated and 82,177 out of 82,621 combinations (99.5%) showed edit distance larger than 5 (Table 4). To examine the range of species that can be amplified using MiBird-U primers, we performed an analysis with the primerTree package [25]. The results confirmed that the primers can amplify avian species (Fig.1b).…”
Section: A Tests Of Versatility Of Designed Primers In Silicosupporting
confidence: 49%
See 2 more Smart Citations
“…In addition, inter-specific differences in the edit distance were calculated and 82,177 out of 82,621 combinations (99.5%) showed edit distance larger than 5 (Table 4). To examine the range of species that can be amplified using MiBird-U primers, we performed an analysis with the primerTree package [25]. The results confirmed that the primers can amplify avian species (Fig.1b).…”
Section: A Tests Of Versatility Of Designed Primers In Silicosupporting
confidence: 49%
“…Thus, by using primerTree package, species whose sequences can be amplified, phylogenetic relationships among these amplified species, and interspecific variations in the amplified sequences are rapidly visualized. Further information and instructions for the primerTree package can be found in Cannon et al [25] .…”
Section: B In Silico Evaluation Of Interspecific Variation Of Mibirdmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these trade‐offs, species biodiversity varies extensively between geographic regions (Abell et al., ; Olson et al., ; Spalding et al., ) which further complicates the selection process as the performance of metabarcoding primers will vary depending on the species composition at the sampling location. In recent years, a number of software programs have been developed for the in silico evaluation of metabarcoding primers (Boyer et al., ; Cannon et al., ; Elbrecht & Leese, ; Ficetola et al., ; Foster, Sharpton, & Grünwald, ; Riaz et al., ). However, most studies to date have only evaluated primers using a single program, and the performance of primer performance has not been evaluated at a regional scale.…”
Section: Introductionmentioning
confidence: 99%
“…No other DNA from tissue extractions used in primer development were identified in our runs. We cannot account for the chicken, turkey or pig sequences contained in our runs; however, other studies have reported reads from these species as well as from cattle and suggest that these reads may have come from animal feed found in aquaria from which samples were taken [25], fecal matter from livestock swept down river [51] or contaminated PCR reagents, particularly dNTPs [35]. We believe that most of the chicken, turkey and pig sequence could have come from our PCR reagents, but further investigation is required.…”
Section: Discussionmentioning
confidence: 99%